Movement of Caribbean peoples...In: Caribbean affairs, 7, (3) July-August, p.128-137. - JONES-HENDRICKSON, S.B. (2011)
Notes that as a result of immigration/migration and emigration, the regional landscape has changed and will continue to change. Claims that the reaction to the changes has been uneven and the policies are not often well thought out.
Keywords: MIGRATION; IMMIGRATION; EMIGRATION; CARIBBEAN